Existence and uniqueness for a semilinear sixth-order ODE - Danet Cristian-Paul (2022)
By using variational methods and maximum principles we discuss the existence, uniqueness and multiplicity of solutions for a semilinear sixth-order ODE. The main difference between our work and other related papers is that we treat a general case and we do not impose sign restrictions on the nonlinearity f or on its potential F.
Keywords: Természettudományok; Matematika